Dissertation Abstracts (Academy of Management Journal, 1963)
The article presents abstracts of dissertations related to management. They include “An Investigation Into the Psychology of Strikes,” by Joel Morris, “An Evaluation of the Application of Electronic Data Processing to Production Control,” by Ross W. Lovell, and “The Role of American Management Consultants in Some of the Middle Eastern Countries,” by Aly Maasarani.